The state of nature: histories of an idea - Somos, Mark; Peters, Anne (Brill, 2022)
List of Illustrations -- Notes on Contributors -- Introduction -- Mark Somos and Anne Peters -- 1 Thucydides, Hobbes, and the Melian Dialogue -- Benjamin Straumann -- 2 Missing Terms in English Geographical Thinking, 1550-1600 -- Mary C. Fuller -- 3 Do Shepherds Live in a State of Nature? From Peculium to Civilization -- Francesca Iurlaro -- 4 After Vitoria Natural Law and the Spanish Ideology of Empire -- Daniel S. Allemann -- 5 Fleeing " Polyphemus 's Den" Locke's State of Nature as Sanctuary -- Ioannis Evrigenis -- 6 Invisible People The State of Nature in Hugo Grotius' Account of Global Legal Order -- Emile Simpson -- 7 From the State of Nature to the State of Economy Pufendorf on Commerce and Natural Law -- David Singh Grewal -- 8 The State of Nature, the Family and the State -- Simone Zurbuchen -- 9 Written in the Hearts of People? Natural and International Law during the Age of Enlightenment -- Edward J. Kolla -- 10 From Natural Equality to Frankpledge The State of Nature, Ancient Constitutionalism, and the Rupture of the Social Contract in Eighteenth-Century Antislavery Writings -- Sarah Winter -- 11 From the State of Nature to the Natural State Transforming the Foundations of Science and Civil Progress in Eighteenth-Century British Political Thought -- Pamela Edwards -- 12 Their Own State(s) of Nature The Enlightenment Social Imaginary and the Invention of Hungarian Ethnic Origins -- László Kontler -- 13 The Place of the Environment in State of Nature Discourses Reassessing Nature, Property and Sovereignty in the Anthropocene -- Tom Sparks -- 14 The State of Nature, Prehistory, and Mythmaking -- Karl Widerquist and Grant S. McCall -- Index.
"We are grateful to the Max Planck Institute for Comparative and International Private Law for providing a supportive institutional setting for this project, and for the opportunity to gather all participants to discuss their chapters and the volume as a whole at the authors workshop in the Harnack House of the Max Planck Society in Berlin in 2019".--ECIP Introduction
Includes bibliographical references and index
Keywords: Konferenzschrift; Geschichte; Naturrecht